Pharmacology for nurses - Smith, Blaine Templar ;Pacitti, Diane (Massachusetts : Jone and Bartlett Learning, 2020)
A Revolutionary New Undergraduate Pharmacology Text for Nursing Students Pharmacology for Nurses is a groundbreaking new text that teaches the basic concepts of pharmacology to undergraduate nursing students. The text focuses on critical need-to-know information and draws on the experience of fourteen contributing authors in the field of nursing. It takes a new approach to teaching the complex topic of pharmacology through its concise, digestible coverage of material, reader friendly design, and use of images and tables to reinforce content. This text is also intended as a reference for other nursing courses and as part of the nursing professional$1 (Bs permanent reference library. Designed to reflect real-life clinical applications, Pharmacology for Nurses also provides a fundamental introduction to pharmacology for nursing students. The basics of pharmacokinetics and pharmacodynamics explained in relation to clinical practice. Patient and drug variables as well as drug interactions and effects are also fully explored along with the administration of medications. Topics Covered: Inter-relationship of physiologic processes Effect of drugs on physiologic processes Homeostatic nature of the body Key Features: Each chapter begins with a summary of Learning Objectives Chapters conclude with summaries and practice questions.s
Introduction to pharmacology -- Introduction to drug action : the interplay of pharmacokinetics and pharmacodynamics -- Medication administration -- Central nervous system drugs -- Autonomic nervous system drugs -- Cardiovascular medications -- Respiratory medications -- Pharmacology of the gastrointestinal tract -- Endocrine system drugs -- Medications for eye and ear disorders -- Pharmacology of the genitourinary system -- Drugs associated with pregnancy, labor and delivery, and lactation -- Pharmacology in dermatologic conditions -- Pharmacology of psychotropic medications -- Pharmacology of anesthetic drugs -- Pharmacology of antimicrobial drugs
Includes bibliographical references and index.
Keywords: PHARMACOLOGY